Research progress on characteristics of secondary aluminum dross and its detoxification and utilization - Kun LIN; Yuanbo ZHANG; Zijian SU; Jiamei XU; Tao JIANG (工程科学学报)
Secondary aluminum dross is a typical hazardous solid waste unavoidably generated during aluminum production and processing. However, it contains not only a large amount of aluminum nitride (AlN), chlorine salts, fluoride, and other hazardous substances but also about 40% (mass fraction) of aluminum, making it a potential aluminum resource with remarkable utilization value. The annual output of secondary aluminum dross in China has estimated to be over 3 million tons based on the aluminum production in 2023. This amount will continue to rise as the amount of recycled aluminum increases. Disposal of secondary aluminum dross has become a problem restricting the development of the aluminum industry. This study reviews the sources and characteristics of secondary aluminum dross, as well as the research progress on the harmless and resourceful utilization of this dross. Moreover, it discusses the future development direction of secondary aluminum dross disposal. The research results show that the pyrometallurgical process focuses on achieving large-scale utilization of secondary aluminum dross with high processing efficiency, with the common end products being cement, refractory materials, calcium aluminate-refining agents, and ceramic heat storage balls, among others. However, owing to the considerable volatilization of salts, the pyrometallurgical process suffers high energy consumption, serious corrosion of equipment, and heavy restrictions on the composition of the raw materials. In contrast, the hydrometallurgical process focuses on achieving harmless utilization of secondary aluminum dross, representing an environmentally friendly and more inclusive detoxification of raw materials. However, the acid and alkali leaching process suffers a large amount of waste liquid discharge, and the water leaching process results in only incomplete removal of AlN, which requires further disposal. Efficient detoxification and large-scale, high-value utilization of secondary aluminum dross can not only eliminate the potential environmental risks caused by stockpiling of hazardous solid wastes but also realize the maximum utilization of aluminum resources; this is of great importance for the ecological environment and healthy development of the aluminum industry. We recommend that secondary aluminum dross be resourced according to its salt content and categorized for disposal. Low-salt secondary aluminum dross can be directly discarded via the pyrometallurgical process. High-salt secondary aluminum dross can be pretreated via the hydrometallurgical process to remove salts and most of the nitrogen, after which the pyrometallurgical process can be employed to realize high utilization of the dross. Meanwhile, the utilization of secondary aluminum dross in high value–added materials such as calcium aluminate-refining slag, ceramic heat storage balls, and refractory materials is strengthened. Without compromising product quality, the proportion of secondary aluminum dross should be added to the greatest possible extent for maximum utilization of valuable elements in the dross. Furthermore, gases such as H2, CH4, and NH3 are unavoidably generated during the hydrometallurgical process; these gases serve as a valuable by-product as well as a potential risk. Hence, methods for regulating the generation of these gases in a targeted manner and efficiently recycling them are also a future direction of study.